Evaluasi Pengelolaan Sampah Menggunakan Pemodelan Sistem Dinamis di Kabupaten Ponorogo - Labibah, Lulu; Pulungan, Muhammad Almaududi (Universitas Al Azhar Indonesia, 2025)
Existing waste management policy in Ponorogo Regency has not been able to achieve the expected target. Understanding the dynamics of the process is necessary to evaluate the current policy for further improvement. Therefore, this study aims to develop a system dynamic model to evaluate the waste management performance in Ponorogo Regency. This study uses Dynamic System Simulation Design to model the waste management through Causal Loop Diagram (CLD) and Stock Flow Diagram (SFD). This research relies on primary data and secondary data, to develop a model that includes 50 variables across three subsystems: Waste Generation, Waste Management, and Waste Management Costs. The simulation results show four waste management scenarios: Business as Usual (BaU), Education Improvement, Facility Improvement, and a Moderate Combined Education-Facility. The Moderate Combined scenario is selected as the best recommendation, which is projected to achieve 94% waste management by 2026, with high investment level but positive long-term impacts. In addition, simultaneous improvements in facilities and public education are necessary to effectively address the waste management issues in Ponorogo, with a focus on enhancing infrastructure and increasing public participation.Keywords - Causal Loop Diagram, Simulation, Stock Flow Diagram, Waste Management.